Analisis Pengaruh Disiplin serta Motivasi Kerja terhadap Kinerja Karyawan pada Departemen Sewing PT. Osha Asia Kabupaten Bogor - Arman Setiyadi; Teul Panda Banjal (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2026)
The purpose of this study is to examine the effect of discipline and work motivation on employee performance in the sewing department of PT. Osha Asia, Bogor Regency. This research uses a quantitative method with a saturated sampling technique involving 56 respondents. Data were analyzed using validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results show that discipline has a significant effect on employee performance, with a coefficient of determination of 53.1% and hypothesis testing indicating that the calculated t value is greater than the t table value (7.811 > 2.005). Work motivation also has a significant effect on employee performance, with a coefficient of determination of 37.6% and hypothesis testing showing that the calculated t value is greater than the t table value (5.708 > 2.005). Simultaneously, discipline and work motivation significantly affect employee performance, as reflected in the regression equation Y = 10.230 + 0.469X1 + 0.273X2. The coefficient of determination is 60.2%, while the remaining 39.8% is influenced by other factors. Hypothesis testing indicates that the calculated F value is greater than the F table value (40.058 > 2.780).